2012
DOI: 10.2519/jospt.2012.3780
|View full text |Cite
|
Sign up to set email alerts
|

Rate of Force Development as an Adjunctive Outcome Measure for Return-to-Sport Decisions After Anterior Cruciate Ligament Reconstruction

Abstract: Study Design Descriptive, prospective, longitudinal single-cohort study. Objective To investigate the rate of force development to 30% (RFD30), 50% (RFD50), and 90% (RFD90) of maximal voluntary isometric contraction (MVIC) as an adjunct outcome measure for determining readiness for return to sport following an anterior cruciate ligament (ACL) reconstruction. Background One criterion of full recovery following an ACL reconstruction is the ability to achieve 85% or 90% of the maximal strength of the contralatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
157
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(167 citation statements)
references
References 42 publications
8
157
1
1
Order By: Relevance
“…19 The ability to produce quick or explosive movements is often more important than muscle strength 19 in sporting activities, and speed rather than magnitude is associated with self-reported physical function in individuals with ACLR. 20 Therefore, the rate of torque development (RTD) is an important indicator of quadriceps function in individuals with ACLR 21 and is associated with greater ground reaction forces and loading rates during walking gait.…”
Section: à6mentioning
confidence: 99%
See 1 more Smart Citation
“…19 The ability to produce quick or explosive movements is often more important than muscle strength 19 in sporting activities, and speed rather than magnitude is associated with self-reported physical function in individuals with ACLR. 20 Therefore, the rate of torque development (RTD) is an important indicator of quadriceps function in individuals with ACLR 21 and is associated with greater ground reaction forces and loading rates during walking gait.…”
Section: à6mentioning
confidence: 99%
“…Injured individuals had undergone unilateral ACLR and were cleared by a physician for participation in physical activity. Uninjured participants were matched to individuals with ACLR on sex, age (61 year), body mass index (61 kg/m 2 ), and Tegner Activity Scale score 21 (61). The university's institutional review board approved the study, and all participants provided written informed consent before data collection.…”
Section: Participantsmentioning
confidence: 99%
“…10 Mean RFD for the reconstructed knees did not reach 90% of preinjury values until 12 months after surgery. 10 ACL injury may limit an athlete's ability to RTP at a high level even after surgical reconstruction and diligent rehabilitation. Survey data indicated that 35% to 57% of recreational athletes were unable to return to their previous sport activities after ACLR.…”
Section: Resultsmentioning
confidence: 99%
“…The ability to generate force quickly during athletics may be important for successful performance and for protection against injury. In a prospective analysis, Angelozzi et al 10 reported that RFD values were only 63% to 80% of preseason/ preinjury values 6 months post-ACLR. 10 Mean RFD for the reconstructed knees did not reach 90% of preinjury values until 12 months after surgery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation